2018
DOI: 10.2478/acph-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin inhibits the growth of bladder carcinoma via deactivation of STAT3

Abstract: Bladder cancer (BCa) is one of the most common urinary cancers. The present study aims to investigate whether Paeoniflorin (Pae) can exert inhibitory effects on BCa. The results showed that Pae inhibited proliferation of human BCa cell lines in a concentration- and time-dependent manner. Pae and cisplatin (Cis) synergistically inhibited the growth of tumours in RT4-bearing mice. Pae treatment neutralized the body loss induced by Cis. Moreover, Pae induced apoptosis in RT4 cells and increased the activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…By inhibiting pathway STAT3, the growth of bladder cancer cells is inhibited . In 2018, Yang et al . carried out both in‐vivo and in‐vitro studies and found that Paeoniflorin inhibits the growth of bladder cancer cells by inhibiting pathway STAT3.…”
Section: Anticancer Activities Of Paeoniflorin and Its Potential Mechmentioning
confidence: 99%
See 2 more Smart Citations
“…By inhibiting pathway STAT3, the growth of bladder cancer cells is inhibited . In 2018, Yang et al . carried out both in‐vivo and in‐vitro studies and found that Paeoniflorin inhibits the growth of bladder cancer cells by inhibiting pathway STAT3.…”
Section: Anticancer Activities Of Paeoniflorin and Its Potential Mechmentioning
confidence: 99%
“…By inhibiting pathway STAT3, the growth of bladder cancer cells is inhibited. [59] In 2018, Yang et al [73] carried out both in-vivo and in-vitro studies and found that Paeoniflorin inhibits the growth of bladder cancer cells by inhibiting pathway STAT3. In addition, another study on red peony root extract (Paeoniflorin), based on in-vivo and in-vitro excitements of Paeoniflorin on mouse bladder cancer cells, shows that the extract maintains the cells in G 1 phase and has no obvious cytotoxicity to other cells, [74] but the specific mechanism is not very clear.…”
Section: Bladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Paeoniflorin (PF), a monoterpene glycoside isolated from the aqueous extract of the Chinese herb Radix Paeoniae alba , is a biologically active compound (Liu, Han, Zhou, & Li, ). Currently, studies on PF mainly focus on its antitumor and neuroprotective effects (Cong et al, ; Yang et al, ; Yu et al, ), having been shown that it can protect neurons in an MPTP mouse model of Parkinson's disease (Zheng et al, ). An antiinflammatory effect of PF has been reported, being involved in preventing endoplasmic reticulum stress‐associated inflammation in lipopolysaccharide‐stimulated human umbilical vein endothelial cells (Li, Jiao, & Xie, ).…”
Section: Introductionmentioning
confidence: 99%
“…38 A RT4 cell xenograft nude mice model was established to determine if PF could inhibit bladder tumor growth in vivo, the results showed that intraperitoneal administration of PF (100 mg kg −1 day −1 ) reduced the weight and volumes of the tumor tissue. 31 Additionally, by oral gavage feeding of PF at 1 g kg −1 day −1 , PF reduced the tumor volume by 30.8% and had a stronger growth inhibitory effect and lower blood toxicity than that of docetaxel. 57 In summary, these studies indicated that PF has a variety of antitumor activities.…”
Section: Anticancer Activity In Vitro and In Vivomentioning
confidence: 98%